Our Experiences with Asparaginase Activity Measurements in Children with Lymphoblastic Diseases - Judit Müller; Petra Egyed; Daniel Erdelyi; Krisztian Kovacs; Katalin Mudra; Sandor Szabo; Balint Egyed; Kovacs Gabor (MDPI AG, 2023)
Background: Asparaginase is a key component of chemotherapy protocols for the treatment of lymphoblastic malignancies among children. Adequate asparagine depletion is an important factor to achieve optimal therapeutic outcomes. Methods: Over a 3.5 year period, 106 patients were monitored for asparaginase activity (329 samples) in a single center of the Hungarian Pediatric Oncology-Hematology Group. In Hungary, three asparaginase products are available: native E. coli ASNase (Kidrolase), a pegylated form of this enzyme (Pegaspargase) and another native product from Erwinia chrysanthemi (Erwinase). A retrospective data analysis was performed. Results: In 81% (268/329) of our patients, AEA levels were in the optimal therapeutic range of over 100 IU/L. Of 106 patients, 13 (12%) were diagnosed with 'silent inactivation'. Conclusions: Monitoring of AEA can help to identify patients with 'silent inactivation' and their asparaginase therapy can thus be optimized.